Peningkatan Kapasitas Kelembagaan dalam Mendukung Ketahanan Pangan Kabupaten Jeneponto - Mudatsir, Rasdiana; Asriyanti Syarif (Jurnal Galung Tropika, 2023)
Strengthening farmer institutions is one of the government's efforts to improve farmer welfare. This research aims to: (1) determine the role of agricultural institutions in supporting the National food security program in Jeneponto Regency; and (2) determine the strategies that need to be implemented in strengthening farmer institutions to support food security programs in Jeneponto Regency. This research was designed with a qualitative approach and analyzed using the SWOT data analysis technique. The informants used in this research came from administrators and members of farmer groups, Agricultural Extension Centers, community leaders, and supporting institutions in agricultural activities. The research results show that the actors who play a role in developing a food security system are farmers who are members of farmer groups, agricultural instructors, and traders. The strategies that need to be implemented in strengthening farmer institutions are improving administration in farmer groups, increasing farmer participation to become independent farmer groups, government support in establishing farmer economic institutions, forming independent agricultural extension workers, increasing the role of farmer groups in using modern technology to add added value. The products produced increase farmers' bargaining position in the agricultural product trade system.